Corporate citizenship perspectives and foreign direct investment in the U.S - Pinkston, Tammie S. (Journal of business ethics, 1994)
As foreign direct investment in the U.S. continues to become both more visible and controversial, the general public remains skeptical about the corporate citizenship of these foreign affiliates. Four dimensions of corporate citizenship — orientations, organizational stakeholders, issues, and decision-making autonomy — were used to compare the inclinations of foreign affiliates with the domestic firms operating in the U.S. chemical industry. The only significant differences between the U.S. sample and those firms headquartered in other countries-of-origin were found in the area of corporate citizenship decision making autonomy.